2019
DOI: 10.1097/mpa.0000000000001367
|View full text |Cite
|
Sign up to set email alerts
|

Defining Pancreatitis as a Risk Factor for Pancreatic Cancer

Abstract: Objectives Acute and/or chronic pancreatitis has been implicated as an important risk factor for pancreatic cancer; however, the incidence and temporal relationship of pancreatitis before pancreatic cancer diagnosis are unclear. We aim to understand the role and incidence of pancreatitis temporally with the development of pancreatic cancer. Methods A population-based study was used to investigate a temporal relationship between pancreatitis and pancreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 14 publications
0
7
0
3
Order By: Relevance
“…Mutations of susceptibility genes in chronic pancreatitis can determine hereditary pancreatitis, idiopathic chronic pancreatitis, and cystic fibrosis, and Cazacu et al [ 140 ] found that mutations of cystic fibrosis transmembrane conductance regulator ( CFTR ) genes modestly increase the risk of pancreatic cancer in a meta-analysis. A total of 50080 patients were diagnosed with pancreatic cancer, of which 14.8% (7420 cases) were diagnosed with idiopathic pancreatitis prior to the diagnosis of cancer[ 141 ]. After pancreatitis diagnosis, six risk factors significantly associated with pancreatic cancer diagnosis included age between 40 and 90 years, African-American race, male sex, smoking, obesity, and DM, suggesting that it may be warranted to screen patients older than 40 years with unclear etiology of pancreatitis, especially for African-Americans and male population[ 141 ].…”
Section: Modifiable Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations of susceptibility genes in chronic pancreatitis can determine hereditary pancreatitis, idiopathic chronic pancreatitis, and cystic fibrosis, and Cazacu et al [ 140 ] found that mutations of cystic fibrosis transmembrane conductance regulator ( CFTR ) genes modestly increase the risk of pancreatic cancer in a meta-analysis. A total of 50080 patients were diagnosed with pancreatic cancer, of which 14.8% (7420 cases) were diagnosed with idiopathic pancreatitis prior to the diagnosis of cancer[ 141 ]. After pancreatitis diagnosis, six risk factors significantly associated with pancreatic cancer diagnosis included age between 40 and 90 years, African-American race, male sex, smoking, obesity, and DM, suggesting that it may be warranted to screen patients older than 40 years with unclear etiology of pancreatitis, especially for African-Americans and male population[ 141 ].…”
Section: Modifiable Risk Factorsmentioning
confidence: 99%
“…A total of 50080 patients were diagnosed with pancreatic cancer, of which 14.8% (7420 cases) were diagnosed with idiopathic pancreatitis prior to the diagnosis of cancer[ 141 ]. After pancreatitis diagnosis, six risk factors significantly associated with pancreatic cancer diagnosis included age between 40 and 90 years, African-American race, male sex, smoking, obesity, and DM, suggesting that it may be warranted to screen patients older than 40 years with unclear etiology of pancreatitis, especially for African-Americans and male population[ 141 ].…”
Section: Modifiable Risk Factorsmentioning
confidence: 99%
“…A large cohort study reported that 14.8% patients with pancreatic cancer had a prior diagnoses of pancreatitis. 34 However, the relationship between pancreatitis and pancreatic cancer has not been completely elucidated. In the present study, we reveal a role for a pro-inflammatory miRNA, miR-301a, in pancreatitis and pancreatitis-associated PanIN, which are conditions known to accelerate the development of pancreatic ductal adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…[31]. По данным A. Syed et al, панкреатит возник у 81,3 % пациентов за 3 мес до постановки диагноза РПЖ и у 98,9 % за 3 года [32]. Таким образом, исследователи пришли к выводу, что хронический панкреатит, как и сахарный диабет, может являться как фактором риска РПЖ, так и быть следствием РПЖ из-за возможной обструкции протоков опухолью и в данном случае может выступать в роли раннего маркера РПЖ.…”
Section: физическая активностьunclassified